Keberpihakan Dan Komunikasi dalam Kebijakan Perlindungan Buruh - Ana Nadhya Abrar (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2002)
This article reviews public policies on labour protection. it argues that those policies do not take the side to the labour. This article suggests that in order to implement those policies, the policy makers should take into count labour communication as a tool of management in the context of making policies on labour protection.